Comprehensive analysis of long noncoding RNAs and mRNAs expression profiles and functional networks during chondrogenic differentiation of murine ATDC5 cells. (17th July 2019) - Wang, Wei; Ding, Yu; Xu, Yanhua; Yang, Hefeng; Liu, Wenjing; Wang, Haixia; Chen, Ceshi; Liu, Rong; Li, Song
Abstract: Chondrogenic differentiation is a coordinated biological process orchestrated by various cell signaling pathways, involving complex pathways regulated at both transcriptional and post-transcriptional levels. Long noncoding RNAs (lncRNAs) are emerging as important regulators in the modulation of multiple cell processes. However, the potential roles of lncRNAs and their regulatory mechanisms in chondrogenic differentiation remain largely unclear. In this study, microarray was performed to detect the expression profiles of lncRNAs and messenger RNAs (mRNAs) during chondrogenic differentiation of murine chondrogenic cell line ATDC5. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to explore their functions. Coding-noncoding co-expression (CNC) and competing endogenous RNA (ceRNA) networks were also constructed with bioinformatics methods. The results revealed that 1009 lncRNAs and 1206 mRNAs were differentially regulated during chondrogenic differentiation. GO and KEGG pathway analysis indicated that the principal functions of the transcripts were associated with system development and extracellular matrix-receptor interaction, TGF-β signaling, and PI3K-Akt signaling pathways. The CNC network showed that lncRNA AK136902 was positively correlated with prostaglandin F receptor (FP). The ceRNA network covered 3 lncRNAs, 121 miRNAs and 241 edges. The upregulated lncRNA AK136902, AK016344, and ENSMUST00000180767 might promote chondrogenic differentiation by acting as ceRNAs. Knockdown of lncRNA AK136902 could inhibit the mRNA expression of FP and other chondrogenic related genes, including Aggrecan and Col2a1 during chondrogenic differentiation. Our results provide a new perspective on the modulation of lncRNAs during chondrogenic differentiation.